2021
DOI: 10.3389/fgene.2021.672804
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Biomarkers Discovery of Methylation Modification With Direct High-Throughput Nanopore Sequencing

Abstract: Cancer is a complex disease, driven by a combination of genetic and epigenetic alterations. DNA and RNA methylation modifications are the most common epigenetic events that play critical roles in cancer development and progression. Bisulfite converted sequencing is a widely used technique to detect base modifications in DNA methylation, but its main drawbacks lie in DNA degradation, lack of specificity, or short reads with low sequence diversity. The nanopore sequencing technology can directly detect base modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Epigenetic modifications are mainly realized by DNA methylation, which has been proven to be a key contributor to the process of tumorigenesis and tumor progression ( Abante et al, 2021 ; Chen et al, 2021a ; Fatima et al, 2021 ; Zhang et al, 2021 ). Through comparing the methylation roles of DLAT in tumors and normal tissues, we found that the levels of DNA methylation were significantly increased in bladder urothelial carcinoma (BLCA), colon adenocarcinoma (COAD), cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC), ESCA, HNSC, prostate adenocarcinoma (PRAD) and rectum adenocarcinoma (READ) ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Epigenetic modifications are mainly realized by DNA methylation, which has been proven to be a key contributor to the process of tumorigenesis and tumor progression ( Abante et al, 2021 ; Chen et al, 2021a ; Fatima et al, 2021 ; Zhang et al, 2021 ). Through comparing the methylation roles of DLAT in tumors and normal tissues, we found that the levels of DNA methylation were significantly increased in bladder urothelial carcinoma (BLCA), colon adenocarcinoma (COAD), cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC), ESCA, HNSC, prostate adenocarcinoma (PRAD) and rectum adenocarcinoma (READ) ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we could adapt our model to quantify the uncertainty about the presence of epigenetic modifications, such an methylation, which are now becoming analyzable in real time with nanopore sequencing (Simpson et al 2017;Leger et al 2021;Liu et al 2021;Zhang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the future we would like to apply our method to a wider array of biological problems. For example, we could adapt our model to quantify the uncertainty about the presence of epigenetic modifications, such an methylation, which are now becoming analyzable in real time with nanopore sequencing (Simpson et al 2017; Leger et al 2021; Liu et al 2021; Zhang et al 2021). In that case we could also inform priors with sequence context, in order to take into account that some modifications such as 5-methylcytosine (5mC) occur most frequently at CpG dinucleotides (Ehrlich et al 1982; Bird 1986).…”
Section: Discussionmentioning
confidence: 99%
“…1 ) [ 13 , 14 ], and detection of DNA methylation [ 15 ]. Due to its fundamental role in cancer, methylation detection offers a unique diagnostics opportunity [ 16 ]. These and other developments are allied with the sensitivity to detect mutants in a 1:100 dilution, as demonstrated in oncological biosensing [ 17 ].…”
Section: Nanopore Sequencingmentioning
confidence: 99%